Risk Factors for Blood Transfusion during Caesarean Section - Aneela Gul Shaikh, Varisha Fatima Shaikh, Muhammad Taha Nasim, Eisha Farid, Shajeea Arshad Ali, Dua Azim, Hadiya Afzal, Kinza Iqbal, Ayman Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the risk factors and evaluate the association of blood transfusion with neonatal outcomes. Study Design: Prospective study Place and Duration of Study: Department of Obstetrics & Gynaecology, Lady Willingdon Hospital, Khairpur Mir’s Pakistan from 1st June 2021 to 31st December 2021. Methodology: Nine hundred and fifty seven women who underwent C-sections were enrolled. The maternal socio-demographics and comorbidities, obstetrics and operative factors, indications for C-section, and neonatal outcomes were recorded. Results: The results revealed that high maternal weight and age, preoperative anemia, placenta previa or abruption, antepartum hemorrhage, third trimester bleeding, multiparity, assisted reproductive technology (ART), prophylactic anticoagulation, and prolonged labor were significantly associated with transfusion during C-section. However, prior uterine scar or atony, previous C-sections, multiple births, diabetes, fibroids, Human immunodeficiency virus (HIV), type of C-section, the cadre of the lead surgeon, surgery type, failed induction or instrumentation, fetal distress, malpresentation, and adhesions were not significantly associated with blood transfusion. There was no significant difference in birth weights of neonates from the two groups. Conclusion: Healthcare professionals should stay cautious when dealing with parturients exhibiting such risk factors. Timely arrangement and transfusion of blood in these women can help reduce maternal mortality.